Investigating the dynamics of actors' formal and informal organizational change communication during mergers and acquisitions - Lim, Kenneth (The University of Edinburgh, 2021)
Mergers and acquisitions (M&As) involve transformational changes and implicate multiple stakeholders at all levels of an organization. Organizations rely on effective communication to deliver the desired merger outcomes and help employees to better cope with the changes of M&As. Yet, the extant literature that is primarily focused on the strategic and financial aspects of M&As lacks nuances in the communicative processes. Through three qualitative research papers, this thesis investigates the various communicative forms, actors, and practices during M&As to shed more light on the phenomenon. This thesis then presents a communication model that helps to inform our understanding of the meaning-making process during M&As. Paper One investigates formal and top-down communication in the early stages of M&As. The study explores the discursive and symbolic construction of early executive formal communication through a qualitative analysis of 23 M&A deal announcements and earnings calls transcripts from 2006 - 2016. Drawing on symbolic management theory, the study unpacks four symbolic significances of executive communication during M&As: Appropriateness (of deals); Superiority (of merged entities); Concern (of the workforce); and Continuity (of implementation). Paper Two examines informal and bottom-up communication at the workforce level during M&As. By analyzing secondary data and 27 semi-structured interviews, the study explores how gossip acted as a resource for employee sensemaking during a recent merger between two professional services firms. The study reveals gossip helped employees to make sense of M&As in three ways: Constituting reactions to shock; Acquiring, deciphering, and synthesizing information; and Providing social support. Paper Three investigates the intersection between communication and HR management during M&As. Through 20 semi-structured interviews with HR Managers, the study explores and examines secrecy-transparency tensions facing HR Managers during M&As. The findings highlight three ways HR Managers managed the tensions by Rebuilding employee trust; Creating a respectful and safe space; and Providing Clarity
Keywords: Mergers and acquisitions; communicative processes; top-down communication; workforce level communication; HR management communication; M&A